MODEL SISTEM PENGELOLAAN MADRASAH BERBASIS ENTREPRENEURSHIP DI KOTA PAREPARE - Muhammad Alwi; Muh Iqbal Andhira; Muhammad Urwa (Jurnal Manajemen Pendidikan, 2026)
This study aims to formulate a management system model for entrepreneurship-based madrasahs in Parepare City as an effort to strengthen institutional independence and innovation in Islamic education. The study is motivated by the limited human resources, inadequate facilities, and high dependence of madrasahs on government funding, while entrepreneurial practices have not been systematically integrated into the management system. This research employed a qualitative approach with a case study design conducted at MAN 1 Parepare and MA DDI Taqwa Parepare. Data were collected through in-depth interviews, observations, and documentation, and analyzed thematically using triangulation techniques. The findings indicate that madrasahs face internal challenges such as limited teacher competence, inadequate facilities, and capital constraints, as well as external challenges including competition and public stigma. However, significant opportunities are identified through students’ vocational skills, stakeholder support, and strategic location. The study concludes that madrasahs are in a developing stage and require strengthening in organizational structure and evaluation systems to achieve sustainable entrepreneurship management.